Sorbaria sorbifolia flavonoid derivative induces mitochondrial apoptosis in human hepatoma cells through Bclaf1 - Chen, Jiaxin; Cheng, Haoyi; Bai, Chunhua; Wang, Dandan; Fu, Jinghao; Hao, Jinge; Wang, Yixuan; Xuewu, Zhang (Frontiers in Pharmacology, 2024)
4',5,7-trihydroxy-8-methoxyflavone was anticancer monomer components isolated from the traditional Chinese medicine Sorbaria sorbifolia. 4 ' , 5-Dihydroxy-7-piperazinemethoxy-8methoxyflavonoids (DMF) with good solubility and anti-tumor effects was obtained by chemical modification in the early stage. This study explored the mechanism by which DMF regulates mitochondrial apoptosis of human hepatoma cells through Bcl-2-associated transcription factor 1 (Bclaf1). DMF inhibited the proliferation of human hepatoma cells in a concentration-and timedependent manner, and DMF induced cells mitochondrial apoptosis. Molecular docking and cell assay results demonstrated that DMF inhibits Bclaf1 expression by binding to the active site of Bclaf1. Lentivirus transfection was used to construct cells with stable knockout and overexpression of Bclaf1 and a Hep3B xenograft model was constructed in nude mice, the mechanism by which DMF induced mitochondrial apoptosis of human hepatoma cells through Bclaf1 was further verified in vitro and in vivo. These findings indicated that DMF induced human hepatoma cells mitochondrial apoptosis through Bclaf1.